2018
DOI: 10.1038/s41424-018-0005-8
|View full text |Cite
|
Sign up to set email alerts
|

Barrett's esophagus is associated with a distinct oral microbiome

Abstract: ObjectivesThe esophageal microbiome is composed of predominantly oral flora and is altered in reflux-related conditions including Barrett’s esophagus (BE). Changes to the esophageal microbiome may be reflected in the oral cavity. Assessing the oral microbiome thus represents a potential non-invasive method to identify patients with BE.MethodsPatients with and without BE undergoing upper endoscopy were prospectively enrolled. Demographics, clinical data, medications, and dietary intake were assessed. 16S rRNA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 46 publications
3
60
0
Order By: Relevance
“…In addition, a study showed that decreased abundance of Proteobacteria and increased abundance of Firmicutes was associated with BE, which was consistent with our findings (Snider et al, 2018). We also observed Veillonella, a core microbiome, was significantly enriched in EC patients.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, a study showed that decreased abundance of Proteobacteria and increased abundance of Firmicutes was associated with BE, which was consistent with our findings (Snider et al, 2018). We also observed Veillonella, a core microbiome, was significantly enriched in EC patients.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, and AUC of 0.9 would indicate that the probability of discriminating a case vs. control is 90%. In Table 1, we show three examples of combined taxons to distinguish controls vs. cancer samples: a three taxon model of Lautropia, Streptococcus and an unspecified genus of the order Bacteroidales, with AUC =0.94, has been associated with esophageal cancer (66), a two taxon model, Streptococcus mitis and Neisseria elongata with an AUC of 0.90, associated with pancreatic cancer (71) and a bacterial cluster associated with gastric cancer with AUC of 0.76 (96). Finally, another approach to the use of biomarkers in differentiating case vs. control samples is using changes in biodiversity indicators as a proxy of changes in the microbiome that could be linked to the status of the sample, independently of what organisms are present or absent.…”
Section: Oral Microorganisms and Cancers Outside The Oral Cavitymentioning
confidence: 99%
“…Oral and esophageal microbial compositions are closely related, possibly due to movement of oral microbes to more distal gastrointestinal sites; 32 as such, it is possible that the associations between dietary fiber and esophageal microbiota may be mediated by effects of fiber or other related factors on the oral microbiome. Similarly, perhaps through association with obesity, fiber intake could be associated with frequency or severity of acid reflux and reflux-associated disease, another factor with known associations with altered upper gastrointestinal microbiome composition 3 , 17 , 33 . On the other hand, dietary fiber could impact the esophageal microbiome via its effects on host metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Patient data and samples used for the current study had been previously collected for a case-control study of the esophageal microbiome in adult patients with and without BE, described elsewhere in detail 17 . Briefly, patients ≥18 years old who were scheduled to undergo upper endoscopy for clinical indications were included.…”
Section: Methodsmentioning
confidence: 99%